SIMULATION OF COLOR VARIATIONS IN GRAVITATIONALLY LENSED QUASAR Q2237+0305 (THE EINSTEIN CROSS) - Smirnov, G. V.; Vakulik, V. G.; Schild, R. E.; Tsvetkova, V. S. (Одеські астрономічні публікації, 2007)
A mechanism of colorized phenomena in gravitationally lensed quasar Q2237+0305 due to microlensing is analysed in computer simulation. A two-component quasar spatial structure model consisting of a hot central source surrounded by an extended outer structure with a more low-temperature radiation was proposed. The model was shown to provide relationship between variations of the (V - I) color indices and R magnitudes, which is consistent to the observed one presented in our recent publication.